The Sybil attack in mobile adhoc network: analysis and detection - Sinha, S; Paul, A; Pal, S (Proceedings of third International Conference on Computational Intelligence and Information Technology, 2013)
Security is one of the most challenging issues in Mobile Adhoc Network (MANET) due to the lack of centralized authority and limited resources. This paper discusses different types of security attacks in MANET and gives emphasis particularly on the Sybil attack which is one of the most harmful attacks. Taxonomy and threats of Sybil attacks in different environment are presented. Comparative analysis has been performed on several detection approaches to mitigate Sybil attack which provides efficiency, limitations and application domain of each of these approaches. This paper also introduces a new approach to detect Sybil attack based on clustering as well as resource testing.